Efficacy of Secukinumab Sustained over Time for Treatment of Active PsA - Nierengarten, Mary Beth (MD Conference Express, 2014)
This article presents the results of the Efficacy at 24 Weeks and Long-Term Safety, Tolerability, and Efficacy up to 2 Years of Secukinumab (AIN457) in Patients With Active Psoriatic Arthritis (PsA) study [FUTURE 1; NCT01392326]. FUTURE 1 is a multicenter, placebo-controlled phase 3 study in which 606 patients with PsA received an intravenous loading dose of secukinumab at 10 mg/kg every 2 weeks for the first 4 weeks, followed by subcutaneous doses of 75 mg (n=202) or 150 mg (n=202) monthly, compared with placebo (n=202).